The Effect of Combined Training on Visceral Fat and Insulin Resistance in Middle-Aged Korean Obese Women - YOON, Mi-Sook; Kim, Eun-Hee; PARK, Hyun-tae; PARK, Sang-Kab; KWON, Yoo-Chan (Journal of Physical Education and Medicine, 2004)
The purpose of this study was to investigate the effect of combined training on visceral fat, insulin resistance and blood lipids among the Korean middle-aged obese. Study subjects were 30 obese women who were divided into three groups: a control group (n=10, mean age 45.7), an aerobic training group (n=10, mean age 46.3) and a combined training group (n=10, mean age 45.7). The aerobic training consisted of 60% Heart Rate Reserve (intensity), 60 min/day (duration) for 6 days/week (frequency). The combined training employed resistance training (3 days/week) and aerobic training (3 days/week). The VO2max was significantly increased in both training groups volumes of abdominal subcutaneous fat and visceral fat decreased more in the combined training group than in the aerobic training group. Lean body mass and growth hormone were significantly increased only in the combined training group. In addition, the homeostasis model assessment (HOMA) index and values for total cholesterol, triglyceride and LDL-C were significantly decreased and the HDL-C level was significantly increased in both groups. In conclusion, we observed that combined training resulted in a much greater reduction of abdominal subcutaneous fat and visceral fat than aerobic training alone. Furthermore, regardless of the type of exercise, regular exercise training will aid in treatment of obesity as well as prevention of life style-related diseases through changes in body composition, serum lipid, abdominal fat and the HOMA index.